2013
DOI: 10.1097/hjh.0b013e3283610fed
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Specificity Protein 1 by CpG hypomethylation upregulates Na+-K+-2Cl− cotransporter 1 in hypertensive rats

Abstract: Our results indicate that recruitment of Sp1 by CpG hypomethylation leads to upregulation of Na⁺-K⁺-2Cl⁻ cotransporter 1 in hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…There are numerous examples demonstrating an impairment of transcription factor binding by site-specific CpG methylation (Cho et al, 2013). In order to investigate whether similar mechanisms exist for some of the downstream targets of SOX6, we assessed the methylation status of CpG dinucleotides adjacent to putative SOX6 binding sites within the MEST upstream regulatory region.…”
Section: E)mentioning
confidence: 99%
“…There are numerous examples demonstrating an impairment of transcription factor binding by site-specific CpG methylation (Cho et al, 2013). In order to investigate whether similar mechanisms exist for some of the downstream targets of SOX6, we assessed the methylation status of CpG dinucleotides adjacent to putative SOX6 binding sites within the MEST upstream regulatory region.…”
Section: E)mentioning
confidence: 99%
“…As such, pharmacological studies have revealed key roles for the ubiquitous NKCC1 and renal specific NKCC2 in vascular and renal cells respectively. NKCC1 are involved in the suppression of myogenic response in microcirculatory beds [45,71] and NKCC2 are involved in blood pressure regulation through sodium reabsorption.…”
Section: Role Of Nkcc In Cardiovascular Diseasementioning
confidence: 99%
“…A histone activating code, acetylated histone H3, was increased and histone repressive code, trimethylated histone H3, was reduced in ang-II infused rats compared to the sham. Studies have shown that the recruitment of specificity protein 1 by CpG hypomethylation leads to the upregulation of NKCC1 in hypertensive rats [71]. This could mean that NKCC1 is epigenetically upregulated by histone modification (P<0.05) or DNA demethylation upon the development of hypertension (P<0.01) and that the methylation of CpG dinucleotides may play a role in the epigenetic maintenance of blood pressure through decreased expression of NKCC1.…”
Section: Nkcc In Vascular Cellsmentioning
confidence: 99%
“…As such, pharmacological studies have revealed key roles for the ubiquitous NKCC1 and renal specific NKCC2 in vascular and renal cells respectively. NKCC1 is involved in the suppression of myogenic response in microcirculatory beds [ 51 , 82 ] and NKCC2 is involved in blood pressure regulation through sodium reabsorption.…”
Section: Role Of Nkcc In Cardiovascular Diseasementioning
confidence: 99%
“…A histone activating code, acetylated histone H3, was increased and histone repressive code, trimethylated histone H3, was reduced in ang-II infused rats compared to the sham infused animals. Studies have shown that the recruitment of specificity protein 1 by CpG hypomethylation leads to the upregulation of NKCC1 in hypertensive rats [ 82 ]. This could mean that NKCC1 is epigenetically upregulated by histone modification or DNA demethylation upon the development of hypertension.…”
Section: Role Of Nkcc In Cardiovascular Diseasementioning
confidence: 99%